2014
DOI: 10.4161/auto.28034
|View full text |Cite
|
Sign up to set email alerts
|

The natural compound oblongifolin C inhibits autophagic flux and enhances antitumor efficacy of nutrient deprivation

Abstract: Metabolic stress induces autophagy as an alternative source of energy and metabolites. Insufficient autophagy in nutrient-deprived cancer cells would be beneficial for cancer therapy. Here, we performed a functional screen in search of novel autophagy regulators from natural products. We showed that oblongifolin C (OC), a natural small molecule compound extracted from Garcinia yunnanensis Hu, is a potent autophagic flux inhibitor. Exposure to OC results in an increased number of autophagosomes and impaired deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
110
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 58 publications
5
110
0
Order By: Relevance
“…Previous phytochemical investigations in our group showed that oblongifolin C (OC) and guttiferone K (GK) are two mainly polyisoprenylated benzophenone derivatives (PPAPs) from G. yunnanensis Hu [1]. The results of our studies revealed further that OC and GK are multi-therapeutic agents with anti-inflammatory and anti-cancer properties [1,[3][4][5][6][7]. Emerging evidence clearly indicated that OC and GK are promising candidates for developing novel treatments for infection or cancer and large amounts of these compounds are needed for further investigations, especially for animal studies [5].…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous phytochemical investigations in our group showed that oblongifolin C (OC) and guttiferone K (GK) are two mainly polyisoprenylated benzophenone derivatives (PPAPs) from G. yunnanensis Hu [1]. The results of our studies revealed further that OC and GK are multi-therapeutic agents with anti-inflammatory and anti-cancer properties [1,[3][4][5][6][7]. Emerging evidence clearly indicated that OC and GK are promising candidates for developing novel treatments for infection or cancer and large amounts of these compounds are needed for further investigations, especially for animal studies [5].…”
Section: Introductionsupporting
confidence: 51%
“…The results of our studies revealed further that OC and GK are multi-therapeutic agents with anti-inflammatory and anti-cancer properties [1,[3][4][5][6][7]. Emerging evidence clearly indicated that OC and GK are promising candidates for developing novel treatments for infection or cancer and large amounts of these compounds are needed for further investigations, especially for animal studies [5]. Without published synthetic route, OC or GK was usually isolated from plants using conventional techniques [1,8] such as repeated silica gel column chromatography, MCI column chromatography, medium-pressure preparative liquid chromatography (MPLC), and preparative HPLC, all of which included complicated, inefficient, and time-consuming operations.…”
Section: Introductionmentioning
confidence: 87%
“…During this process, autophagosomes engulf damaged proteins and defective organelles and then fuse with lysosomes for degradation (9). Finally, the unnecessary proteins are removed, the flawed organelles are eliminated and the cell growth is sustained during conditions of stress through autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, many natural products have been reported to able to cause cancer cell death by regulating the functional status or signal pathways of autophagy (Ajabnoor et al, 2012;Lao et al, 2014;Larocque et al, 2014). In this article, the application of representative natural products in cancer treatments and their action modes associated with autophagy signal pathway have been reviewed and discussed in an attempt to inspire the promising treatment strategies for cancers in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, natural compounds are expected to become potential effective drugs for the prevention and treatment of cancers in the future. In vitro and in vivo studies have shown that many dietary agents from fruits, tea and some herbs with both medicinal and food functions are able to fight against and prevent cancers via regulating cellular fate through apoptosis and autophagy (Kallifatidis et al, 2013;Kma, 2013;Lachumy et al, 2013;Zhong et al, 2013;Lao et al, 2014;Larocque et al, 2014).…”
Section: Introductionmentioning
confidence: 99%